Primary cutaneous lymphomas: diagnosis and treatment - Sokołowska-Wojdyło, Małgorzata; Olek-Hrab, Karolina; Ruckemann-Dziurdzińska, Katarzyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Primary cutaneous lymphomas (CLs) are a heterogeneous group of lymphoproliferative neoplasms, with lymphatic proliferation limited to the skin with no involvement of lymph nodes, bone marrow or viscera at the diagnosis. Cutaneous lymphomas originate from mature T-lymphocytes (65% of all cases), mature B-lymphocytes (25%) or NK cells. Histopathological evaluation including immunophenotyping of the skin biopsy specimen is the basis of the diagnosis, which must be complemented with a precise staging of the disease and identification of prognostic factors, to allow for the choice of the best treatment method as well as for the evaluation of the treatment results.